O que há de público na política pública?: análise do processo de elaboração do programa de revitalização e desenvolvimento da região central histórica de Santos a partir de narrativas - Bittencourt, Lúcio Nagib (2010)
Starting from the following research question, “what is the public in the public policy”, this thesis, on the elaboration process of the Revitalization and Development Program of Santos Historic Center, also known as Alegra Centro, intends to identify what perspectives of the public are taking place at the themefield, having as methodological approach the collection and study of narratives. Centered on two particular issues, the interaction between local government and civil society, as well as the role played by local cultural aspects in the narratives, breakdowns were found, picturing conflicts into the process under study. The main contributions of this work are to propose a particular look for public policies on historic center revitalization from the Public Administration field, to use a narrative approach in order to study public policies and to construct a mystery for the particular case that should be solved by future investigations.